Storytelling otherwise: Decolonising storytelling in planning. (May 2023) - Ortiz, Catalina
This article argues that the role of storytelling in planning needs to be rethought learning from the decolonial turn in social sciences. I ask how to decolonise storytelling in planning theory and practice. The aim is to explore how key notions from Latin American decolonial thinking, such as pluriverse, epistemological disobedience, border thinking and sentipensar, can help us to reframe storytelling in planning. This reframing can contribute to finding different avenues to build ontological relationality in a framework of epistemological justice and healing to bring about new imaginations for shaping urban planning otherwise.